Implementasi Bimbingan dan Konseling dalam Meningkatkan Motivasi Belajar Siswa Kelas XI di Sekolah Menengah Kejuruan Santa Monika Kabupaten Kubu Raya - Florentina Florentina (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2021)
The purpose of this study is to answer: how is the implementation of guidance and counseling in Class XI Santa Monika Vocational High School, Kubu Raya Regency? What are the supporting and inhibiting factors in an effort to motivate students to learn in Class XI at Santa Monika Vocational High School, Kubu Raya Regency? How are the efforts made by the Guidance and Counseling teacher in providing student motivation in Class XI at the Santa Monika Vocational High School, Kubu Raya Regency? The results showed that the implementation of guidance and counseling in increasing the motivation of class XI students at SMK Santa Monika was carried out in orientation services, information services, distribution placement services, content mastery services, individual counseling services, group guidance services, group counseling services, consulting services, mediation, and advocacy services. The guidance and counseling service program is still not optimal. Supporting factors from the implementation of guidance and counseling by the school and supporting teachers by making guidance and counseling service programs. Inhibiting factors are the shortage of teachers or counselors, limited time, and teachers who teach are not used to teaching in class. Efforts made by guidance and counseling teachers in increasing learning motivation are recording children by filling in student identities, experiencing or approaching students, making individual or group programs and providing suggestions to class XI students at SMK Santa Monika, Kubu Raya Regency.